O BNB e o desenvolvimento do nordeste brasileiro: Velhas e novas miss\~oes para uma economia em mudança - Aristides Monteiro Neto; Fernando Cezar de Macedo; Raphael de Oliveira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The study investigates the role of Banco do Nordeste do Brasil (BNB) as a financing agent for regional development policy (PNDR). Initially, it brings a brief discussion on ways of acting public development banks (BD) in the contemporary world. The analytical effort then focuses on identifying the sectoral and territorial applications of the disbursements of the Constitutional Financing Funds (FCFs) managed by BNB for the period 1995-2019 and how they target promising activities for structural change. When investigating the geography of total and sectoral disbursements through state and microregional data, territorial patterns prevail in the period. We seek to point out whether and how the Bank approaches or distances itself from structural change strategies consistent with those that are, in our view, the central challenges of the northeastern and Brazilian economy.
10419/284893
Keywords: O18; O43; R11; R58; 330; regional development; public banks; public finance